Credit Depth on Indonesian Regional Economic Development - Sipahutar, Mangasa Augustinus (Universitas Negeri Malang, 2018)
From regional perspective, the role of banks credit is important to encourage the economic real sectors. Local government spending aimed to enhancing regional economic growth, if supported by adequate banks credit will encourage regional economic growth. Using VAR model revealed that provinces showed different responses to the causality between credit depth and regional economic growth. Panel data analysis revealed, there is a positive relationship between regional credit depth and real regional economic growth percapita, and 68 percent of real regional economic growth percapita can be explained by credit depth. Increasing credit depth by 1 basis point will increase regional economic growth by 0.03 basis points. Furthermore, increasing credit depth by 1 basis point in t-1, will reduce regional poverty by 0.16 basis points in period t. The model showed that 23 percent of the variance of poverty can be explained by credit depth in the previous year. Keywords: credit depth, economic growth, regional economic developmentJEL Classification: E61; G28; O23